Dental rehabilitation of cleft palate patients using zygomatic implants: A case report - Teresa Creo-Martinez; Maitena Canivell-Zabaleta; Alba Sanjuan-Sanjuan; Manuel Caro (SAGE Open Medical Case Reports)
Edentulous patients with history of cleft palate and severe maxillary atrophy are challenging patients to rehabilitate through an oral approach. The difficulty of rehabilitating these patients lies in the unusual anatomy they present and the alteration of the vascular supply of local tissues caused by the previous performed surgeries, along with other causes. This report describes the successful dental rehabilitation with zygomatic implants of a patient with complete bilateral cleft palate who was edentulous and had severe maxillary atrophy.